The added value of modern Decision Support Systems (DSS) against forest fires in a global scale - Stavros Sakellariou; Stergios Tampekis; Fani Samara; Olga Christopoulou (European Regional Science Association (ERSA), 2015)
Forest fires constitute one of the greatest hazards for the viability and sustainable development of forests with consequences both on natural and cultural environment, undermining the economy and the quality of life of local and regional populations. The outbreaks of forest fires could stem from either natural or anthropogenic causes. The latter usually compose the greatest percentage of ignition of forest fires especially at the Mediterranean regions. The best strategic to grapple with forest fires while taking under consideration both functional and economic efficiency is considered of primary importance. To this effect, great share have the usage and adoption of decision support systems (DSS) which contain tools of G.I.S. and satellite technology and function as information systems which support the managers responsible for eliminating the forest fires. DSS make up a valuable tool for prevention and fighting against forest fires and lately they are adopted at growing rate at global level. The basic models-subsystems which comprise the structural elements for confronting forest fires and most DSS use are the following: 1) Retrieval, analysis, update, edit and prediction models of geospatial (geomorphology - topography, socioeconomic and environmental data), meteorological and satellite data, 2) Risk indexes and thematic maps (past fire incidents - records, moisture data etc.) of indigenous vegetation and forest fuel, 3) Fire propagation and behavior models and 4) Utilizing of interactive programs for the preparation, plans establishing, coordination and prompt dispatch of specific forces of the fire department (human force, land or aerial firefighting forces or even a combination). Definitely, the sub-systems of the most DSS can be used independently depending on the main purpose, such as for prevention or suppression procedures; for the financial estimation of the planned mission; for the smoke detection and the prediction of its repercussions on the human health etc. Hence, the paper aims to a comparative assessment of the most contemporary DSS which are in use in different geographic scales -such as national and federal level- as well as to a thorough exploration of the effectiveness and contribution of such systems to the confronting of forest fires.
Keywords: 330; forest fires; decision support systems; g.i.s.; remote sensing